Malpraktik Pemilu dan Korupsi: Analisis terhadap Proses Penghitungan dan Rekapitulasi pada Pemilu Indonesia 2019 - Luthfi Hamzah Husin; Heroik Mutaqin Pratama; Wegik Prasetyo; Hendra Hendra; Wawan Budi Darmawan; Firman Manan; Feri Amsari (Komisi Pemberantasan Korupsi, 2021)
This article attempts to examine the relationship between election malpractice and corruption by focusing on analyzing frauds in the vote counting and recapitulation process in the 2019 Indonesian Election, specifically in the legislative election. This study tries to fill in the gaps in literature that examines electoral malpractice in Indonesia which is seen more at the campaign stage rather than the vote counting and recapitulation stages in which the role of election management body is very central. To analyze this, this study analyses more specifically the involvement of the General Election Commission (KPU) as election organizer in electoral malpractice. Using document analysis and case study method, this study found that the vote recapitulation stage, especially at the district level, is the most prone phase to electoral malpractice where the involvement of the ad-hoc election administrator and candidates’ witness play an important role there.